HUBUNGAN KEKUATAN OTOT DENGAN KESEIMBANGAN DINAMIK PADA LANSIA DI POLI RAWAT JALAN FISIOTERAPI RS HUSADA UTAMA SURABAYA - Qodariyah, Himmatul; Pradita, Angria; Zakaria, Amin; Fariz, Achmad (NHM PRESS, 2023)
As we age, body tissues are often subjected to structural and functional changes. Decreased muscle mass is a true sign of decreased function in the elderly. This has an impact on body balance in old age. There are two types of body balance: dynamic balance, where the body can maintain proper posture while moving, and static balance, where the body can maintain the center of gravity to support the body in an upright position while standing. The purpose of this study was to analyze the relationship between muscle strength and dynamic balance in the elderly at the physiotherapy outpatient clinic of Husada Utama Hospital Surabaya. The method of this study was cross sectional with a sample size of 30 elderly people who met the inclusion and exclusion criteria by measuring muscle strength using Manual Muscle Testing and dynamic balance using the Timed Up and Go Test. The results of this study found that muscle strength was 5 at most with 7 respondents and balance values at the age of 66-69 years with normal values > 10 seconds as many as 8 respondents. The correlation test results show that the p-value is 0.008. The conclusion that can be obtained from this study is that there is a relationship between muscle strength and dynamic balance in the elderly at the outpatient clinic of Husada Utama Surabaya Hospital.